G. Stanley Hall on “Mystic or Borderline Phenomena” - Alvarado, Carlos S (Journal of Scientific Exploration, 2014)
G. Stanley Hall (1844–1924) was one the most prominent of the early American psychologists and an outspoken skeptic about the existence of psychic phenomena. This article presents a reprint of one of his critiques on the topic, a little-known paper entitled “Mystic or Borderline Phenomena” published in 1909 in the Proceedings of the Southern California Teacher’s Association. Hall commented on some phenomena of physical mediumship, as well as on apparitions, telepathy, and mental healing. In his view all could be explained via conventional ways such as trickery and the workings of the unconscious mind. The paper is reprinted with an introduction and annotations providing biographical information about Hall and additional information and clarification of the points he made in the paper. It is argued that Hall’s paper represents an instance of boundary-work common at the beginning of organized psychology, representing an attempt to give authority to the discipline over fields such as psychical research.